Communication to the Editor—The Cluster Plan for Desegregating Public Schools, or a Little Less Weltanschauung, Please, for Some More Adequate Descriptions - Cooper, W. W. (Management Science, 1976)
It may not be possible to be wholly objective, as Messrs. Stimson and Thompson (among others) assert (see [Stimson, D. H., R. P. Thompson. 1975. The importance of ‘Weltanschauung’ in Operations Research: The case of the school busing problem. Management Sci. 21 (10, June) 1123–1132.]). Nevertheless, one should be as objective as possible in OR, or any other science, and this carries with it the concomitant duty of accurate and adequate descriptions—including descriptions of work by others to the extent that it may be pertinent.